Diatom boron isotope data from ODP Site 882 over the intensification of Northern Hemisphere Glaciation - Donald, Hannah; Swann, George E A; Rae, James W B; Foster, Gavin L (PANGAEA, 2024)
Diatom boron and boron isotope data from ODP Site 882 in the subarctic Pacific Ocean over the intensification of Northern Hemisphere glaciation (iNHG) at 2.73 Ma.
Keywords: Boron isotope; Diatom; ODP Site 882